IMPLEMENTASI PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN MEDIA KARMILA SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA - Rospala Hanisah Yukti Sari (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The implementation of media in mathematics learning is still rarely implemented due to the lack of knowledge about learning media, so its implementation is quite limited. There is a need for learning media that can connect abstract mathematical concepts with students' understanding of mathematical concepts. One of the efforts made is implementing Realistic Mathematics Education assisted by KARMILA media (Training Mini Cards). This research aims to provide a description of improving student learning outcomes in implementing a realistic mathematics approach assisted by KARMILA media. The subjects of this research were class IV B students at SD Negeri 6 Palangkaraya, totaling 23 students. This type of research is Classroom Action Research (PTK). Data collection techniques using tests. The research method used is a mix method, namely qualitative and quantitative. The results of the research show that student learning outcomes when taking action using the Realistic Mathematics Approach assisted by KARMILA media in class IV B of SD Negeri 6 Palangka have increased. This can be seen from the student test results where in cycle II, the average student learning outcome score was 85 with a classical completeness score of 96%. So, it can be concluded that there is an increase in mathematics learning outcomes by using the Realistic Mathematics Approach assisted by KARMILA media in class IV B of SD Negeri 6 Palangkaraya.